2016
DOI: 10.17294/2330-0698.1053
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Causing Fungi in Homes and Yards in the Midwestern United States

Abstract: Journal of Patient-Centered Research and Reviews ( JPCRR) is a peerreviewed scientific journal whose mission is to communicate clinical and bench research findings, with the goal of improving the quality of human health, the care of the individual patient, and the care of populations. Recommended CitationBaumgardner DJ. Disease-causing fungi in homes and yards in the Midwestern United States. J Patient Cent Res Rev. 2016;3:99-110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 95 publications
(117 reference statements)
0
7
0
1
Order By: Relevance
“…31 Malassezia pachydermatis fungemia has occurred as outbreaks in neonatal intensive care units, including one case in which the employee acquired the strain from a household dog. 49 Sporotrichosis (discussed in detail in previous articles 1,2 in this series) may be a zoonotic infection in some cases. 10 There have been epidemiologic associations of this disease with armadillo hunting, fire-ant bites and contact with domestic cats infected with Sporothrix schenckii.…”
Section: Zoonotic Dermatophyte and Nondermatophyte Fungal Infectionsmentioning
confidence: 85%
“…31 Malassezia pachydermatis fungemia has occurred as outbreaks in neonatal intensive care units, including one case in which the employee acquired the strain from a household dog. 49 Sporotrichosis (discussed in detail in previous articles 1,2 in this series) may be a zoonotic infection in some cases. 10 There have been epidemiologic associations of this disease with armadillo hunting, fire-ant bites and contact with domestic cats infected with Sporothrix schenckii.…”
Section: Zoonotic Dermatophyte and Nondermatophyte Fungal Infectionsmentioning
confidence: 85%
“…Residence in close proximity to auto-related businesses was associated on univariable analysis only. As reviewed elsewhere in this issue, 24 many studies, but not all, 42 found outdoor occupations made up a minority of blastomycosis cases. There have been reports of blastomycosis cases in autoworkers based on short case series or case studies, 37,[43][44][45] but no systematic investigation of this connection.…”
Section: Discussionmentioning
confidence: 95%
“…As summarized elsewhere in this issue 24 --although some have demurred 25,26 --there appears to be good circumstantial evidence that blastomycosis can be acquired on one's home property. [27][28][29][30][31] For these reasons, we used home addresses of blastomycosis cases to explore environmental associations of this disease in our previous Wisconsin studies.…”
Section: Geodemographic Features Of Human Blastomycosis In Eastern Wimentioning
confidence: 99%
“…1,2 In this third article of the series, we will review the much less common occurrence of human fungal infections resulting from freshwater exposure. These infections often involve immunocompromised hosts, but may occur following water-associated trauma (either in freshwater or in the presence of freshwater such that associated organisms may enter the body).…”
Section: Freshwater Fungal Infectionsmentioning
confidence: 99%
“…5,6 or those specifically involving household plumbing (covered previously). 2 However, we will restrict this report to diseases acquired from freshwater sources in the natural environment or more generally from tap water. Additionally, while waterrelated fungal infections from developing nations may be used as examples, this review will focus on diseases that would potentially occur in developed nations like the United States.…”
Section: Freshwater Fungal Infectionsmentioning
confidence: 99%